Heterogeneity in Growth and Desistance of Alcohol Use for Men in Their 20s: Prediction from Early Risk Factors and Association with Treatment. (18th October 2012) - Capaldi, Deborah M.; Feingold, Alan; Kim, Hyoun K.; Yoerger, Karen; Washburn, Isaac J.
Abstract : Background: The course of men's alcohol use from ages 18 to 19 through 28 to 29 years was examined using growth mixture modeling (GMM) to determine alcohol trajectories for 3 conceptualizations of alcohol use: volume of use, heavy episodic drinking (HED), and drinking‐related problems. Trajectory classes were validated against the young men's alcohol treatment history, and childhood/adolescent predictors of trajectory membership were examined. Methods: Participants were 205 men from the Oregon Youth Study, an ongoing longitudinal study of predominantly White men recruited from higher crime neighborhoods who were assessed annually during their 20s. The multivariate association between 3 prospectively assessed risk factors—parental alcohol use, child antisocial behavior, and age at first drunken experience—and the latent classes extracted from the GMM were examined for each alcohol indicator. Results: A 3‐class‐solution model best fit the data for each alcohol indicator. The classes for both HED and problematic drinking for the men were significantly associated with history of treatment for alcohol use. Overall, the findings indicated a relatively large class with persistently high volume of alcohol use across the 20s and a greater prevalence of desistance for HED and alcohol problems. Age at first intoxication was the best predictor of latent class membership, and men in the initially high‐then‐desisting alcohol classes had a high level of early risk. Concordance of trajectory class membership across alcohol indicators was moderate overall but particularly strong for higher problem groups, as almost all men in the increasing HED trajectory were also in the highest volume and alcohol problems trajectory classes. Levels of treatment were high for the higher and desisting HED and alcohol problems classes. Conclusions: Many of the men showed chronic alcohol use across the decade of the 20s and had problems resulting from their high usage. Whereas most of the men showed low and/or desisting HED across this period, desistance was less common for volume of use and for alcohol problems.